Effect of the versatile bifunctional chelator AAZTA5 on the radiometal labelling properties and the in vitro performance of a gastrin releasing peptide receptor antagonist - Michael Hofstetter; Euy Sung Moon; Fabio D'Angelo; Lucien Geissbühler; Ian Alberts; Ali Afshar-Oromieh; Frank Rösch; Axel Rominger; Eleni Gourni (SpringerOpen, 2020)
Abstract Background Gastrin Releasing Peptide receptor (GRPr)-based radioligands have shown great promise for diagnostic imaging of GRPr-positive cancers, such as prostate and breast. The present study aims at developing and evaluating a versatile GRPr-based probe for both PET/SPECT imaging as well as intraoperative and therapeutic applications. The influence of the versatile chelator AAZTA5 on the radiometal labelling properties and the in vitro performance of the generated radiotracers were thoroughly investigated. The GRPr-based antagonist D-Phe-Gln-Trp-Ala-Val-Gly-His-Sta-Leu-NH2 was functionalized with the chelator 6-[Bis (carboxymethyl)amino]-1,4-bis (carboyxmethyl)-6-methyl-1,4-diazepane (AAZTA5) through the spacer 4-amino-1-carboxymethyl-piperidine (Pip) to obtain AAZTA5-Pip-D-Phe-Gln-Trp-Ala-Val-Gly-His-Sta-Leu-NH2 (LF1). LF1 was radiolabelled with gallium-68 (PET), indium-111 (SPECT, intraoperative applications) and lutetium-177 (therapy, SPECT). In vitro evaluation included stability studies, determination of lipophilicity, protein-binding studies, determination of Kd and Bmax as well as internalization studies using the epithelial human prostate cancer cell line PC3. In vitro monotherapy as well as combination therapy studies were further performed to assess its applicability as a theranostic compound. Results LF1 was labelled with gallium-68, indium-111 and lutetium-177 within 5 min at room temperature (RT). The apparent molar activities (Am) were ranging between 50 and 60 GBq/μmol for the 68Ga-labelled LF1, 10-20 GBq/μmol for the 111In- and 177Lu-labelled LF1. The radiotracers were stable for a period of 4 h post labeling exhibiting a hydrophilic profile with an average of a LogDoctanol/PBS of − 3, while the bound activity to the human serum protein was approximately 10%. 68/natGa-LF1, 177/natLu-LF1 and 111/natIn-LF1 exhibited high affinity for the PC3 cells, with Kd values of 16.3 ± 2.4 nM, 10.3 ± 2.73 nM and 5.2 ± 1.9 nM, respectively, and the required concentration of the radiotracers to saturate the receptors (Bmax) was between 0.5 and 0.8 nM which corresponds to approximately 4 × 105 receptors per cell. Low specific internalization rate was found in cell culture, while the total specific cell surface bound uptake always exceeded the internalized activity. In vitro therapy studies showed that inhibition of PC3 cells growth is somewhat more efficient when combination of 177Lu-labelled LF1 with rapamycin is applied compared to 177Lu-laballed LF1 alone. Conclusion Encouraged by these promising in vitro data, preclinical evaluation of the LF1 precursor are planned in tumour models in vivo.